Population pharmacokinetic analysis of acetaminophen overdose with immediate release, extended release and modified release formulations. (3rd October 2022) - Spyker, Daniel A.; Dart, Richard C.; Yip, Luke; Reynolds, Kate; Brittain, Scott; Yarema, Mark
Abstract: Objectives: The introduction of delayed release formulations of acetaminophen (APAP) has created concern about the role of formulation in overdose. We examined the APAP overdose pharmacokinetic (PK) profiles to assess the role of dose, coingestants and formulation: immediate release (IR), extended release (ER), and modified release (MR) on APAP pharmacokinetic measures. Methods: We collected by-subject APAP PK data: subject description, timed blood APAP concentrations, dose, and coingestants. We sought both overdose and randomized controlled trials (RCTs) for supratherapeutic doses involving ER or MR formulations. Data analysis and simulation used the non-linear mixed-effects modeling program NONMEM-version 7.4. Results: The final dataset comprised 3, 033 [APAP] from 356 subjects and 15 sources including 3 RCTs (179 subjects receiving IR, 122 ER, 65 MR). The final population PK (PopPK) model was a linear 2-compartment model with first-order (oral) absorption. Covariate relationships included: APAP absorption rate and bioavailability decreased with increased oral dose ( p  < 0.00005) for all 3 formulations (MR > ER > IR). Post hoc analyses showed opioid coingestant increased exposure (area under the curve, AUC) by factor of 1.6. Simulations of 100 g vs 10 g doses for IR, ER and MR showed overdose of the ER formulation exhibits slower absorption and lower C max, overall exposure (AUC) is less than 80% of an equivalent dose of IR acetaminophen. The overall exposure for the MR formulation is less than 70% of an equivalent dose of IR. Conclusions: Acetaminophen ER and MR formulations have slower absorption and decreased bioavailability leading to a lower C max and later T max than the IR formulation. These results have potential clinical implications because delayed absorption could confound use of the Rumack-Matthew nomogram by underestimating the severity of ingestion early in the course of treatment.